Pharmacologic treatment of infants with neonatal abstinence syndrome in community hospitals compared to academic medical centers. (December 2018) - Friedman, Hayley; Parkinson, Gregory; Tighiouart, Hocine; Parkinson, Catherine; Tybor, David; Terrin, Norma; Lester, Barry; Harvey-Wilkes, Karen; Davis, Jonathan
Abstract Objective To compare length of hospital stay (LOS), LOS due to neonatal abstinence syndrome (NAS), and duration of pharmacologic treatment in community or academic settings. Study design One hundred-two infants exposed to opioids in utero at two community hospitals were compared to 256 from eight academic centers. All infants were managed with non-pharmacologic care followed by similar pharmacologic treatment options. Results Two hundred-twelve infants received pharmacologic treatment for NAS. Mean LOS (24.7 ± 8.5 vs. 24.5 ± 11.3 days), LOS due to NAS (24.0 ± 8.2 vs. 23.3 ± 9.2 days), and duration of NAS treatment (19.3 ± 8.0 vs. 18.9 ± 9.2 days) were similar in community compared to academic medical centers. Conclusions No significant differences were found in infants managed in the community compared to academic care settings. These findings support caring for opioid-exposed infants in both community and academic settings with the use of standardized care protocols.